Sociolinguistics perspectives on gender patterns in instagram - Sri Yuliani; Arimuliani Ahmad; Ikel Srinoviati (Journal of Education and Learning (EduLearn), 2020)
This article focused on the the gender patterns that were found in the social media Instagram based on the sociolinguistics point of view. There were two research questions were arisen what types of the gender patterns that were found in the social media Instagram based on the sociolinguistics and the factors of the difference language used based on gender in social media Instagram. Uses and Gratifications Theory (UGT) was used to analyze the data. The data was taken from all of component of the sociolinguistics aspect in social media network especially for gender patterns that existed on the social media instagram college students’ users id in Pekanbaru. The writer took 30 Instagram users id as sample. The study found that two types of gender patterns, first; gender in writing and second; gender in profile photo, thus there were five main assumptions that caused the differences language in gender in social media Instagram, namely; (1) an audience is active and goal-oriented in their media consumption, (2) media are used for gratifications, (3) media are in competition with other means of need satisfaction, (4) people understand their personal media use, interests, and motives enough to communicate with researchers about their choices, (5) the audience members are the only people who can make judgments regarding the value of the media content. The study recommends that sociolinguistics is an interesting topic to be researched thus future field of study concerns with the rapid changing phenomena in social media.